Clinical Evaluation of a New Ayurvedic Herbo-Mineral Formulation (NIA/DG/2020/01) in Stage -1 Primary Hypertension (AYUSHDHARA, 2023)
Hypertension, also known as high or raised blood pressure, is a multifactorial disease with multiple causes and multiple treatments. In India, the prevalence of hypertension was estimated to be 40.8% in urban areas and 17.9% in rural areas. Though there are multiple treatment of disease still it is a challenge to manage this disease effectively with lower side effects as all available treatments are full of side effects and toxic effects. New Ayurvedic herbo-mineral formulation NIA/DG/2020/01 is a new anti-hypertensive Ayurvedic Ghan formulation, containing Arjuna (Terminalia arjuna Roxb.), Ashwagandha (Withania somnifera Linn.), Jatamansi (Nordostachys jatamansi DC.), Shankhpushpi (Convolvulus pluricaulis Chois.), Punarnava (Boerhavia diffusa Linn.), Gojihwa (Onosma Bracteatum Wall.), Guduchi (Tinospora cordifolia Willd.), Mukta Shukti (Margarita) and Praval Pisti (Corrallium Rubrum). Aim and Objective: To assess role of a new Ayurvedic herbo-mineral formulation NIA/DG/2020/01 in Stage-1 primary hypertension. Material and Methods: Initially, the formulations were prepared by the instructions mentioned as per classical text. Then clinical trial was proceeded after ethical clearance and CTRI registration on 60 patients from NIA Arogyashala as per inclusion-exclusion criteria and other said parameters. Observation and Results: Recorded systolic and diastolic blood pressure was tabulated and analysed statistically by SPSS in both the trial groups. Discussion: The result of systolic and diastolic blood pressure changes and percentage of relief was discussed thoroughly. Conclusion: The trial drugs showed highly significant reduction in Blood pressure of stage -01 Hypertension when given at a dose of 1 capsule twice a day before meal for 90 days.